THE INFLUENCE OF SUMMARIZING TECHNIQUE AND READING MOTIVATION TOWARD READING COMPREHENSION ACHIEVEMENT FOR THE SEVENTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL 18 PALEMBANG - Rifdah Nafiilah; Indawan Syahri; Mulyadi (Esteem Journal of English Education Study Programme, 2024)
The aim of this study was to determine whether there is a significant difference in reading comprehension between students who are taught a summarizing technique and those who are not. Additionally, the study sought to determine whether there is a significant difference in reading comprehension between students who are taught a summarizing technique and those who have low reading motivation. The students in the seventh grade at Junior High School 18 Palembang were divided into two groups. In this investigation, factorial design was used. The study's population consisted of all 238 seventh-grade students enrolled in Junior High School 18 Palembang during the academic year 2023–2024. Saturation sampling was used to take samples from 68 students: 34 students from the VII.7 class were in the experimental group, while 34 students from the VII.6 class were in the control group. The researcher used a questionnaire to gather data in order to evaluate students' reading motivation. She also used traditional and summarizing techniques to teach students reading comprehension skills. The data were then analyzed using IBM SPSS Statistics. The study's findings demonstrated a substantial difference in reading comprehension between students who were taught a summarizing strategy and those who were not, with regard to seventh-grade students at Junior High School 18 Palembang. The students with high reading motivation were taught the technique.